VARIASI IMF CONE ANGLE DAN IMF CLOCK ANGLE TERHADAP SIKLUS MATAHARI DAN BADAI GEOMAGNETIK - Izza Fadiyah, Afia
Interplanetary magnetic field (IMF) carried by solar wind and rooted at corona. IMF parameters, sunspot number, and geomagnetic index are downloaded from OMNIWeb which the data is obtained from several spacecraft in geocentric orbits. Solar cycle based on solar magnetic activity is measured in terms of variations in the number of sunspot and its polarity, and it gives a great impact to space weather. Both magnetic events of IMF and sunspot indicate the relation between solar cycle and IMF orientation which is clock angle and cone angle. IMF also interact with Earth’s magnetosphere and it can cause the geomagnetic storms. Cone angle and clock angle are derived from IMF components on X-axis, Y-Axis, and Z-axis. Their frequency distribution charts on each solar cycle of 20 to 24 and its maximum phase and minimum phase are the key point for the analysis. The comparison between sunspot number distribution with cone angle and clock angle on the same maximum and minimum phase were used to be an addition for the analysis. The plot of clock angle and cone angle as a function of Dst index as a geomagnetic index for each solar cycle were also derived. Based on the analysis, solar cycle is indicated gives an impact to the magnitude of each IMF components. It makes the peak of the charts shifted from minimum phase to maximum phase. Other than that, the reconnection in magnetopause can also occur when the cone angle is between 450-900 and when the clock angle is between -360-290. The reconnection when IMF Bz northward is dominant become interesting to be analyzed further.